Regionalization of the Concentration Index in northern Chile and its relation with the orographic component (1966-2015) - Baltazar Fernández, Alexis; Meseguer-Ruiz, Oliver (Investigaciones Geográficas, 2019)
This paper analyzes the spatial distribution of irregularity of daily rainfall in northern Chile (from 17° to 29° S), applying the concentration index (CI). The CI was calculated for a total of 161 meteorological stations, and for the period 1966 to 2015. The purpose was to generate a spatial regionalization of the CI, a daily rate which measures the irregularity of rainfall. Theoretically, a hypothesis was tested that indicates the effect of topography would have on CI, causing an increase in the rate from the coastal plains to zones of higher altitude like the Andes Mountains, and a west-east increasing gradient. The results obtained do not account for an increase to the east as expected, but they show a zonal component characterized by a north-south increasing gradient. Moreover, the daily precipitation CI results allowed the identification of four regions that share similar CI values: the northern zone, with CI values between 0,45 and 0,58; the southern zone, with high rainfall concentrations with values between 0,49 and 0,74; the highlands, with values between 0,45 and 0,67; and the coastal zone, with values between 0,45 and 0,64.